The Promise of Targeting Hypoxia to Improve Cancer Immunotherapy: Mirage or Reality? - Janji, Bassam; Chouaib, Salem (Frontiers in Immunology, 2022)
Almost all solid tumors display hypoxic areas in the tumor microenvironment associated with therapeutic failure. It is now well established that the abnormal growth of malignant solid tumors exacerbates their susceptibility to hypoxia. Therefore, targeting hypoxia remains an attractive strategy to sensitize tumors to various therapies. Tumor cell adaptions to hypoxia are primarily mediated by hypoxia-inducible factor-1 alpha (HIF-1α). Sensing hypoxia by HIF-1α impairs the apoptotic potential of tumor cells, thus increasing their proliferative capacity and contributing to the development of a chaotic vasculature in the tumor microenvironment. Therefore, in addition to the negative impact of hypoxia on tumor response to chemo- and radio-therapies, hypoxia has also been described as a major hijacker of the tumor response by impairing the tumor cell susceptibility to immune cell killing. This review is not intended to provide a comprehensive overview of the work published by several groups on the multiple mechanisms by which hypoxia impairs the anti-tumor immunity and establishes the immunosuppressive tumor microenvironment. There are several excellent reviews highlighting the value of targeting hypoxia to improve the benefit of immunotherapy. Here, we first provide a brief overview of the mechanisms involved in the establishment of hypoxic stress in the tumor microenvironment. We then discuss our recently published data on how targeting hypoxia, by deleting a critical domain in HIF-1α, contributes to the improvement of the anti-tumor immune response. Our aim is to support the current dogma about the relevance of targeting hypoxia in cancer immunotherapy.